1978
DOI: 10.1007/bf00225350
|View full text |Cite
|
Sign up to set email alerts
|

Recent observations on the ultrastructure of human urothelium

Abstract: An electron microscopic study of normal bladder urothelium of elderly patients ranging in age from 61 to 82 years has shown the occurrence of unusually thin regions consisting of either one or two layers of undifferentiated cells interspersed between 3--4 cell layers thick regions. A morphometric study has confirmed the existence of a pattern of cytodifferentiation in cells of the thick region. The generally microvillous nature of the luminal surface is attributed to incompletely differentiated cells that have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1980
1980
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The fine structure of normal adult human urinary bladder epithelium has been described in detail elsewhere.7.iS. 17,2324 Briefly , the luminal membrane of superficial cells appeared as a symmetric unit membrane which was approximately 10 nm thick4*17.23 and was coated with a glyc~calyx. '~ Asymmetric unit membrane plaques, which are prominent in non-primates but not adult humans,'fi were infrequently encountered in adults in the age group (e.g.. fifth to seventh decade) in which urinary bladder carcinoma is most preval-ent.2,4.…”
Section: Ultrastridcture Of Control Epitheliimimentioning
confidence: 99%
“…The fine structure of normal adult human urinary bladder epithelium has been described in detail elsewhere.7.iS. 17,2324 Briefly , the luminal membrane of superficial cells appeared as a symmetric unit membrane which was approximately 10 nm thick4*17.23 and was coated with a glyc~calyx. '~ Asymmetric unit membrane plaques, which are prominent in non-primates but not adult humans,'fi were infrequently encountered in adults in the age group (e.g.. fifth to seventh decade) in which urinary bladder carcinoma is most preval-ent.2,4.…”
Section: Ultrastridcture Of Control Epitheliimimentioning
confidence: 99%
“…Elderly patients are at increased risk for voiding dysfunction. While many of these problems are secondary to other diseases, there are those who have no apparent predisposing factor for their voiding difficulties [Brocklehurst, 19731. To examine this issue, the effect of aging on the urinary bladder has been studied at the light microscopic and ultrastructural levels [Monney and Hinman, 1974;Jacob et al, 1978;Phillips and Davies, 19801. However, these investigations have failed to provide any insight into the possible cause of voiding dysfunction in the otherwise normal aged patient.…”
Section: Introductionmentioning
confidence: 99%
“…Our light-microscopic study does not allow a lysosomal or cytosolic location of the reaction precipitate to be discriminated. Previous electronmicroscopic studies have shown that lysosomes are tightly packed in this supranuclear cytoplasm and that only small cytoplasmic areas between them are free of these organelles (Jacob et al 1978;Holstein et al 1994). Thus, the SOD-reaction product may be distributed within the free cytoplasmic areas between the large lysosomes of the supranuclear region of the superficial cells; this location might contribute to the granular appearance of the reaction product.…”
Section: Discussionmentioning
confidence: 91%
“…The results of the present study show that TRAP is localized within the apical cytoplasm of the superficial cells. In contrast, light-and electronmicroscopic enzyme histochemical studies have revealed that the enzyme activity of the tartrate-sensitive acid phosphatase (isoenzyme ACP2 or conventional lysosomal acid phosphatase) is located within large lysosomes or lysosomal complexes of the supranuclear cytoplasm of the superficial cells (Hicks 1966;Jacob et al 1978;Holstein et al 1994). Since the TRAP activity of other cells is also found in lysosomes (Drexler and Gignac 1994), it seems likely that the product of the immunocytochemical staining in the urothelial superficial cells is located within the acid-phosphatase-positive small lyso- somes and endocytotic vesicles of the subplasmalemmal cytoplasm, as shown by Holstein et al (1994).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation